PRINSIP PENGGEMBALAAN DALAM MAZMUR 23 - Waharman, Waharman (Manna Rafflesia, 2015)
There are many writings that deal with shepherding. In this article we discuss" Shepherding Principles "based on the perspective of Psalm 23. The psalmist stresses the importance of understanding the shepherding principle. In this discussion will explain the psalmist's understanding and principles about shepherding. So that through this paper contribute to developing the principles of shepherding.